Quality of Acute Care and Long-Term Quality of Life and Survival: The Australian Stroke Clinical Registry. Issue 4 (April 2017) - Cadilhac, Dominique A.; Andrew, Nadine E.; Lannin, Natasha A.; Middleton, Sandy; Levi, Christopher R.; Dewey, Helen M.; Grabsch, Brenda; Faux, Steve; Hill, Kelvin; Grimley, Rohan; Wong, Andrew; Sabet, Arman; et al.
Abstract : Background and Purpose—: Uncertainty exists over whether quality improvement strategies translate into better health-related quality of life (HRQoL) and survival after acute stroke. We aimed to determine the association of best practice recommended interventions and outcomes after stroke. Methods—: Data are from the Australian Stroke Clinical Registry during 2010 to 2014. Multivariable regression was used to determine associations between 3 interventions: received acute stroke unit (ASU) care and in various combinations with prescribed antihypertensive medication at discharge, provision of a discharge care plan, and outcomes of survival and HRQoL (EuroQoL 5-dimensional questionnaire visual analogue scale) at 180 days, by stroke type. An assessment was also made of outcomes related to the number of processes patients received. Results—: There were 17 585 stroke admissions (median age 77 years, 47% female; 81% managed in ASUs; 80% ischemic stroke) from 42 hospitals (77% metropolitan) assessed. Cumulative benefits on outcomes related to the number of care processes received by patients. ASU care was associated with a reduced likelihood of death (hazard ratio, 0.49; 95% confidence interval, 0.43–0.56) and better HRQoL (coefficient, 21.34; 95% confidence interval, 15.50–27.18) within 180 days. For those discharged from hospital, receiving ASU+antihypertensive medication provided greater 180-day survival (hazard ratio, 0.45; 95% confidence interval, 0.38–0.52) compared with ASU care alone (hazard ratio, 0.64; 95% confidence interval, 0.54–0.76). HRQoL gains were greatest for patients with intracerebral hemorrhage who received care bundles involving discharge processes (range of increase, 11%–19%). Conclusions—: Patients with stroke who receive best practice recommended hospital care have improved long-term survival and HRQoL. Abstract : Supplemental Digital Content is available in the text.